Retention of the “first-trial effect” in gait-slip among community-living older adults - Liu, Xuan (GeroScience, 2017)
“First-trial effect” characterizes the rapid adaptive behavior that changes the performance outcome (from fall to non-fall) after merely a single exposure to postural disturbance. The purpose of this study was to investigate how long the first-trial effect could last. Seventy-five (≥ 65 years) community-dwelling older adults, who were protected by an overhead full body harness system, were retested for a single slip 6–12 months after their initial exposure to a single gait-slip. Subjects’ body kinematics that was used to compute their proactive (feedforward) and reactive (feedback) control of stability was recorded by an eight-camera motion analysis system. We found the laboratory falls of subjects on their retest slip were significantly lower than that on the novel initial slip, and the reactive stability of these subjects was also significantly improved. However, the proactive stability of subjects remains unchanged between their initial slip and retest slip. The fall rates and stability control had no difference among the 6-, 9-, and 12-month retest groups, which indicated a maximum retention on 12 months after a single slip in the laboratory. These results highlighted the importance of the “first-trial effect” and suggested that perturbation training is effective for fall prevention, with lower trial doses for a long period (up to 1 year). Therefore, single slip training might benefit those older adults who could not tolerate larger doses in reality.